2017
DOI: 10.14710/nusa.12.4.256-264
|View full text |Cite
|
Sign up to set email alerts
|

Judgement Sebagai Sistem Appraisal dalam Iklan Kecantikan Visual Media Cetak

Abstract: This papper investigated the appraisal system used in the verbal message advertisements visual beauty of each print media. Verbal message visual beauty of each print media were analyzed using appraisal theory which found on domain: attitude. Attitude as negotiating meaning to answer research problems. Judgement as the appraisal which dominate the verbal message advertisement visual beauty of the print media. This study is qualitative and interpretative in which the data analyzed using analysys of appraisal fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Attitudes related to three types of evaluations of: a) affect (affect or feelings), b) judgment (judgment), and c) appreciation (appreciation). From several studies that can be used as references by researchers to conduct this research (Nur & Hadi, 2016;Pusparini, Djatmika, & Santosa, 2017;Santosa, 2014;Tiani, 2017). Martin & White (2005) stated that appreciation devices involved evaluations of semiotic and natural phenomena.…”
Section: Linguistics Devices' Appreciation In Semarang's Online Cuisimentioning
confidence: 99%
“…Attitudes related to three types of evaluations of: a) affect (affect or feelings), b) judgment (judgment), and c) appreciation (appreciation). From several studies that can be used as references by researchers to conduct this research (Nur & Hadi, 2016;Pusparini, Djatmika, & Santosa, 2017;Santosa, 2014;Tiani, 2017). Martin & White (2005) stated that appreciation devices involved evaluations of semiotic and natural phenomena.…”
Section: Linguistics Devices' Appreciation In Semarang's Online Cuisimentioning
confidence: 99%
“…From the paper, the emotions in the song build the relationship between the songwriter and the reader [12]. The article used the appraisal system to analyze the visual beauty drawn in verbal message advertisements [14]. Her paper revealed that appraisal tools dominate moral judgment with the positive character as a praise and negative one as a criticism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the research only focused on novel (Dewi, 2015), state political speech (Sukma, 2018;Alvionita, 2018;Rohmawati, 2016), advertisment text (Yunus, 2018;Nugraheni, 2011;Tiani, 2017), information media on tourism (Suryaningtyas, 2018), application of appraisal in teaching (Mustadi, 2010) language evaluation (Panggabean & Lestari, 2018) and online media. Research on the appraisal system particularly in online media has also been carried out by several researchers, such as Nur & Hadi (2017), Pusparini, A., Djatmika & Santosa (2017), Nazhira, R., Sinar, S & Suriyadi, S. (2016), and Ellyawati (2016).…”
Section: Chart 1: Appraisal System (Martin and White 2005)mentioning
confidence: 99%